A compact dual‐band 2 × 1 metamaterial inspired mimo antenna system with high port isolation for LTE and WiMax applications. Issue 8 (15th May 2017) - Panda, Asit K.; Sahu, Sudhakar; Mishra, Rabindra K.
Abstract: This article proposes a compact (43 × 26 × 0.8 mm 3 ) dual‐band two‐element metamaterial‐inspired MIMO antenna system with high port isolation for LTE and WiMAX applications. In this structure, each antenna element consists of a square–ring slot radiator encircling a complementary split ring resonator. A tapered impedance transformer line feeds these radiating apertures and shows good impedance matching. A 2 × 3 array of two‐turn Complementary Spiral Resonator structure between the two antenna elements provides high dual‐band isolation between them. The fabricated prototype system shows two bands 2.34 – 2.47 GHz (suitable for LTE 2300) and 3.35 – 3.64 GHz (suitable for WiMAX). For spacing between two antennas of 10 mm only, the measured isolation between the two antenna elements in the lower band is around −32 dB while that in the upper band is nearly 18 dB. The system shows a doughnut‐shaped radiation patterns. The peak measured antenna gains for the proposed MIMO system in the lower and higher bands are 3.9 and 4.2 dBi, respectively. The MIMO system figure of merits such as the envelope correlation coefficient, total efficiency are also calculated and shown to provide good diversity performance.